First record and new species of the Oriental leafhopper genus Trifida Thapa & Sohi (Hemiptera: Cicadellidae: Typhlocybinae) from China - Huang, Min; Kang, Juxia; Zhang, Yalin (Zootaxa, 2018)
The Oriental leafhopper genus Trifida Thapa & Sohi, 1986 and T. quadripunctata are recorded from China for the first time. Three new species, T. eleganta, T. robusta and T. elongata spp. nov., are described and illustrated. A check-list and key to all species of Trifida are provided.